Issues in the history and character of the Islamic built environment - Spahic, Omer (IIUM, 2005)
The Islamic built environment is the one whose form, design and function are inspired by Islam, are permeated with the Islamic spirit, and stand for the embodiment of the Islamic principles and values. The Islamic built environment came about to facilitate, foster and stimulate the ceaseless ‘ibadah (worship) practices of its users. It was as responsive to material requirements as any other built environment expression, yet it never treated them apart from exigencies of a higher order. By means of skill, creativity and imagination, and by its distinctive combination of aesthetic and utilitarian ends, the Islamic built environment never appeared to be inclined to dissociating man’s corporeal, psychic and spiritual needs. Function lies at the core of the Islamic built environment. Size, together with the overall physical appearance, is inferior and matters only when it comes into complete conformity with the criteria underpinning the essence of the Islamic built environment, when it – for instance – stimulates and bolsters function and utility. This unassuming book discusses several vital, yet often misunderstood, themes pertaining to the history and character of the Islamic built environment. The themes discussed are: 1. An Introduction to the Character of Early Islamic Architecture (from 11 H / 632 CE to 97 H / 715 CE); 2. A Reading of the Philosophy of Rich Decoration in Islamic Architecture; 3. City Planning in Ibn Khaldun’s Thought; 4. Some Housing Planning Policies of the Prophet Muhammad (pbuh ): the Case of the Housing Area Surrounding the Prophet’s Mosque in Madinah; 5. The Significance of the Rock (Sakhrah) Inside the al-Aqsa Mosque; 6. Socio-Political Conditions Surrounding the Creation of the Dome of the Rock; 7. The Holy Qur’an on the Built Environment;